Genre Analysis of Online Encyclopedias: The Case of Wikipedia - Tereszkiewicz, Anna (Jagiellonian University Press, 2014)
The book is the first complete discussion of the genre of online encyclopedias. The first part of the book, preceded by a theoretical introduction into the concept of webgenres, gives a detailed overview of the types of encyclopedic websites, presenting the characteristics of their content, form and functionality. The second part of the publication concerns Wikipedia - the most popular online encyclopedia. The presentation of the structure of the portal is followed by an in depth discussion of Wikipedia discourse features, describing the most conspicuous properties of the stylistic layer of this encyclopedia. The value of the book is additionally enhanced by many illustrations reproducing the analyzed websites.